EXPERIENCE OF IMPLEMENTATION OF MICROPROCESSOR-BASED CONTROL FOR ADJUSTABLE GATE VALVE - Hlushchenko, H. A.; Zaloznyi, V. V.; Davydenko, A. K. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2021)
The article discusses the features of the implementation of an automated control system for the process of recording the parameters of model hydraulic parts of horizontal centrifugal pumps. The design features of the electric actuator and the control gate valve, which complicate the control process, are given. A method to overcome the dead zone, backlash, nonlinearity of the character-istics of the controlling member is proposed. It is shown that high values of the dead zone, backlash, and nonlinearity of the valve characteristics are not an obstacle to change the flow rate of the pumped fluid within small ranges. An example of overcoming the design shortcoming of the gate valve by using control algorithms is given. The algorithmic sequence of gate valve control is described.